Impact of Body Habitus on Operative Difficulties during Extraperitoneal Laparoscopic Radical Prostatectomy - Weimin, Yu; Haga, Nobuhiro; Yanagida, Tomohiko; Kurita, Noriaki; Akihata, Hidenori; Kojima, Yoshiyuki (Urology Journal, 2016)
Purpose: The aim of the present study was to investigate whether patients’ body habitus affects the operative difficulties associated with extraperitoneal laparoscopic radical prostatectomy (LRP). Therefore, the associations between body habitus and perioperative outcomes of surgery, including bleeding, operative time, and resection margins, were evaluated. Materials and Methods: Between August 2010 and July 2012, 40 consecutive patients with preoperative magnetic resonance imaging and abdominal X-ray examinations underwent extraperitoneal LRP for localized prostate cancer at our institution. The associations between anthropometric measurements and demographics of patients, operation duration, estimated blood loss (EBL), and resection margins were analyzed retrospectively. Multivariate analyses were performed, and P < .05 was considered significant. Results: On multiple regression analysis, the view of the prostatic apex (VPA) was significantly associated with EBL (P = .02), and body mass index (BMI) was significantly associated with operative time (P = .02). On multiple logistic regression analysis, protrusion of the prostate into the bladder was significantly associated with positive resection margins (P = .04). Conclusion: The findings of the present study suggest that poor VPA, protrusion of the prostate into the bladder, and high BMI were related to operative difficulties in extraperitoneal LRP. If operative difficulty is predicted preoperatively, it would be better to prepare blood for transfusion and/or special instruments (e.g. flexible scope), or switch to other therapeutic procedures.